Quichuamyia, a new Neotropical genus of Stratiomyidae (Insecta: Diptera) - Brammer, Colin A. (Zootaxa, 2005)
A new Neotropical genus of Stratiomyidae, Quichuamyia gen. nov., is described and illustrated, including the two new species, Quichuamyia aplanatantennae sp. nov. and Quichuamyia costaricensis sp. nov.